Stations of the Cross featured in the Church - Mumbai Archive Project Team (Jio Institute, 2024)
Our Lady of the Rosary church features Stations of the Cross, also known as the Way of Sorrows or the Via Crucis. These are a series of scenes depicting Jesus Christ on the day of his crucifixion. The Stations of the Cross are associated with the Christian themes of repentance and mortification of the flesh.